The structure of the lexical personality descriptors in Serbian language - Smederevac Snežana; Mitrović Dušanka; Čolović Petar (Psihologija, 2007)
Two studies, both originating from a larger psycholexical study in Serbian language, are presented here. Two questionnaires, Lexi and PL have been constructed in the psycholexical study. The questionnaires differ by the formulation of their respective items: while the items of the Lexi contain adjectives, the items of the PL are in the form of statements. The first study presented in this paper examines the latent structure of the Lexi questionnaire, while the second one deals with the latent structure of the PL. In both studies, principal component analysis was applied, and the number of components to be retained in the analysis was determined according to the Scree criterion. Also, Promax rotation was applied in both studies. Seven components which were extracted in the first study have been interpreted as Negative Valence, Negative Emotionality, Aggressiveness, Conscientiousness, Positive Emotionality, Positive Valence and Openness to Experience. The content of these dimensions is obviously similar to the dimensions of Tellegen and Waller’s Big Seven model. In the second study, five components were extracted, and interpreted as Sociability, Anxiety, Aggressiveness, Activity and Impulsivity. The content of the dimensions extracted in the second study corresponds with the dimensions of Marvin Zuckerman’s Alternative Five - Factor Model.